Procedural aspects of police activity in emergency situations (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Mass riots, acts of terrorism, accidents and fires, disasters and natural disasters have a strong and devastating impact on public safety and the environment. The probability of occurrence and severity of the negative consequences of emergency situations may increase, both as a result of new technologies and in the process of active human and citizen life. A holistic approach to risk management based on practical knowledge learned from the lessons of accidents in the past, an understanding of the need for better planning in case of possible emergencies and the implementation of a number of preventive measures should help reduce the number and severity of the consequences of accidents. In turn, the activities of law enforcement agencies to investigate the circumstances of the commission of criminal acts in emergency situations have a number of characteristic features arising fromthe need to establish not only the criminal acts themselves, but also the conditions under which they were committed. This procedure is based on the fact that these conditions, in case of emergency, often entail an increase in the degree of public danger of the act, affecting its criminal legal qualification and sentencing. In order to reveal the true essence of what was done in such a situation, it is necessary to establish it together with the general conditions for the commission of the act.
Keywords: organization, investigation, crime, emergency, law enforcement agencies, criminal procedure law, stages, stages, investigative actions